Typeical Singapore : tracing Singapore's history through vernacular typography - Effendy, Wynne Celina (2018)
Typography plays a part in shaping a nation’s identity. Stories are told through typography around us that create a sense of place of where we live. The everyday street type displays many letterings that carry stories of significant change and culture of the place. Singapore is a country that is constantly improving and changing, thus Typeical Singapore hopes to preserve the types in the heartland before they are lost or replaced. This project also seeks to explore Singapore’s history, urban culture and future planning through the lens of typography, contributing towards the visual identity landscape of Singapore. The result of the research findings would be presented in both digital and print publication which would include a series of typography designs that reflect the character of each of the chosen areas in Singapore. It would furthermore act as a guide that introduces the history of Singapore to both the residents and visitors